VO2 kinetics and tethered strength influence the 200-m front crawl stroke kinematics and speed in young male swimmers - Sokołowski, Kamil (2022)
The aim of this research was to examine the relationship between the fast component of oxygen consumption developed in 1-min V_O2 and force indices both measured in tethered swimming test and to assess the influence of the gathered indices on speed and swimming kinematics in 200-m front crawl race. Methods: Forty-eight male swimmers (aged 13.5 ± 0.9 years old) participated in this study. Testing included 1) 1-min all-out front crawl tethered swimming while oxygen consumption (breath by breath) and tethered forces were measured, 2) 200-m front crawl race-like swimming featuring kinematic analysis, and 3) biological age (BA) examination. Results: During the 1-min all-out tethered swimming test, a linear increase in oxygen consumption was observed. There were moderate to high partial correlations between particular periods of seconds in the 1-min V_O2: 31–60, 41–60, and 51–60 and Fmax, Fave, and Iave of tethered swimming, while 41–60 and 51–60 V_O2 were moderately to highly interrelated with all the swimming speed indices and SI. The swimming speed indices significantly interplayed with SL, SI, Fmax, Fave, and Iave. Partial correlations were computed with BA control. Conclusion: The ability of reaching a high level of V_O2 fast is essential for a swimmer’s energy production at short- and middle-distance events. Reaching a high level of V_O2 significantly determines tethered strength and swimming kinematics. The level of V_O2 influences the maintenance of a proper pulling force and the stroke technique of front crawl swimming in young male swimmers.